Sports pilates how to prevent and overcome sports injuries - Massey, Paul 1963- (Cico Books, 2004)
Olympic adviser Paul Massey reveals a Pilates workout for suppleness, strength and stamina in this volume. In addition he presents a series of problem-busting tips and exercises that show the reader how to prevent and control common sports injuries